Preclinical anticancer studies on the ethyl acetate leaf extracts of Datura stramonium and Datura inoxia - Bakht Nasir; Muhammad Waleed Baig; Muhammad Majid; Syeda Masooma Ali; Muhammad Zafar Irshad Khan; Syeda Tayyaba Batool Kazmi; Ihsan-ul Haq (BMC, 2020)
Abstract Background Cancer is a horrific disease relentlessly affecting human population round the globe. Genus Datura encompasses numerous species with reported medicinal uses. However, its potential as a source of natural anticancer agents is yet to be determined. Datura stramonium (DS) and Datura inoxia (DI) are the two species chosen for this study. Methods Total phenolic and flavonoid content (TPC and TFC) as well as antioxidant activity were assessed through colorimetric method. Polyphenolic quantification was done by RP-HPLC. Following extract standardization ethyl acetate leaf extracts of both species (DSL-EA and DIL-EA) were chosen for anticancer studies. In vitro cytotoxicity using various models including cancer cell lines was monitored. Following toxicity studies, benzene (0.2 ml) was used to induce leukemia in Sprague-Dawley rats. Extracts were orally administered to preventive (100 and 200 mg/kg) and treatment (200 mg/kg only) groups. The antileukemic potential of extracts was assessed through haematological, biochemical, endogenous antioxidants and histological parameters. Results Significant TPC and TFC were estimated in DSL-EA and DIL-EA. RP-HPLC quantified (μg/mg extract) rutin (0.89 ± 0.03), gallic acid (0.35 ± 0.07), catechin (0.24 ± 0.02) and apigenin (0.29 ± 0.09) in DSL-EA while rutin (0.036 ± 0.004) and caffeic acid (0.27 ± 0.03) in DIL-EA. Both extracts exhibited significant brine shrimp cytotoxicity (LC50 < 12.5 μg/ml). DIL-EA exhibited greater cytotoxicity against PC-3, MDA-MB 231 and MCF-7 cell lines (IC50 < 3 μg/ml in each case) as well as higher protein kinase inhibitory action (MIC: 25 μg/disc) compared to DSL-EA. Leukemia induced in rats was affirmed by elevated serum levels of WBCs (7.78 ± 0.012 (× 103) /μl), bilirubin (7.56 ± 0.97 mg/dl), Thiobarbituric acid reactive substances (TBARs) (133.75 ± 2.61 nM/min/mg protein), decreased RBCs (4.33 ± 0.065 (× 106)/μl), platelets (344 ± 3.19 (× 103)/μl), total proteins (2.14 ± 0.11 g/dl), Glutathione S-transferases (GST) (81.01 ± 0.44 nM/min/ml), endogenous antioxidant enzymes levels and abnormal liver and kidney functionality in disease control rats. Both species revealed almost identical and significant (p < 0.05) alleviative effects in benzene induced leukemia. Conclusion Comprehensive screening divulged the tremendous potential of selected species as potent source of natural anticancer agents in a variety of cancers particularly leukemia. Present study might provide useful finger prints in cancer research and mechanistic studies are prerequisite in logical hunt of this goal.